(untitled) (مجلة جامعة اللاذقية - سلسلة الآداب والعلوم الانسانية, 2018)
حازم القرطاجني مثله مثل بقية شعراء الأندلس الذين فتنوا بجمال الأندلس، وطبيعتها فتناول كل ما فيها من رياض، وأزهار، وأنهار، وأرض، وسماء، وحيوان، معتمداً على الحواس مسقطاً على الطبيعة الصفة الإنسانية. وفي هذا البحث، نحاول إلقاء الضوء على الأثر الذي خلفته الطبيعة ومكوناتها في شعر حازم. حيث يشتمل البحث على: مقدمة تتضمن نظرةً سريعةً عن شخصية حازم، وثقافته، وإمكانياته الشعرية، ونحاول إظهار دور الطبيعة في إبداع الشاعر، وأثر البيئة في هذا الإبداع، ويتناول البحث بعد ذلك عناصر الطبيعة في شعر حازم وأولها: الرياض، فنجد حازماً يطنب في وصفها، ويوسّع في أبعاد صورتها ويتعمق في تفاصيلها. وثاني العناصر هو الأزهار، إذ نجد حازماً يكثر من ذكر الأزهار ذات الروائح العطرة، كالخيري، والياسمين، والسوسن، وأزهار اللوز وغيرها. ثم نبحث في العنصر الطبيعي الثالث وهو الماء، حيث نجد صور النهر تجلب المتعة والإعجاب، ونعرّج على وصف حازم للطبيعة العلوية، من بدر وكواكب ومطر وبرق ورعد ومن العناصر الطبيعة التي تناولها حازم الحيوان، فنلحظ في مصادر صوره الحيوان المفترس، كالأسد، والذئب، والثعلب، وغيرها كالظبي، والحداة، والبوم، ولكل دوره في عالم شعره. ثم نتناول طبيعة تونس وحضارتها وأثرها في شعر حازم، حيث يستقي صور القصور والمباني الحضارية مشاهد شعرية جميلة. ثم يحاول البحث التفريق بين الصور المستقاة من الطبيعة الأندلسية والطبيعة التونسية. أمّا الخاتمة فتتضمن أهم النتائج التي توصل إليها البحث. Hazem al – Karajan, as the rest of Amdalusian poets, was charmed by the beauty of Andalus its nature. he dealt with all its gardens flowers, rivers, grounds, sky and animal, depending on senses and enveloping mature the human quality. I m this search, we try to focus the effects which mature and its contents left on Hazem,s poetry. This search contains. Am introduction includes quick view on Hazem,s character,his education and poetic abilities. We try to reveal the role of mature in the poet creation, and the effect of environment in this creation. The search deals with mature elements in Hazem poetry after that. Gardens: we find Hazem describe them widely and enlarge their picture in details.The second element is the flowers. We see Hazem increases in his mention of flowers which have mice odors as al khairi, jasmine, al sawsan, peach flowers and others. Then we look for the third matural element, that is, water. We find the pictures of the river bring joy and admiration. Then we move to Hazem,s description to the upper mature as the moon the, the planets, the rain, the lightning and the thunder. The last element of mature which Hazem dealt with the animal. We notice in the source of his pictures the wild animal as the lion, the wolf, the fox and others as the deer, the owl and each one its role in the world of Hazem poetry. Then we move to Tunisian mature and civilization and its effects in Hazem poetry. He finds he pictures and modern buildings mice poetic views. After that, the search tries to differentiate between the pictures of the Andalusian mature and those the Tunisians. The conclusion includes the most important results which the search reached.